The singularity is near : when humans transcend biology - Kurzweil, Ray. (New York : Viking, 2005)
The futurist Ray Kurzweil is a controversial advocate for the role of machines in the future of humanity. In his latest, thrilling foray into the future, he envisions an event - the "singularity" - in which technological change becomes so rapid and so profound that our bodies and brains will merge with our machines."
Includes bibliographical references (p. 497-602) and index.
Keywords: Brain -- Evolution; Human evolution; Genetics; Nanotechnology; Robotics